Frontal QRS‐T Angle and the Risk of Atrial Fibrillation in the Elderly. Issue 2 (12th August 2016) - Jogu, Hanumantha R.; O'Neal, Wesley T.; Broughton, Stephen T.; Shah, Amit J.; Zhang, Zhu‐Ming; Soliman, Elsayed Z.
Abstract : Background: Frontal QRS‐T angle reflects changes in regional action potential duration and the direction of repolarization. Although it has been suggested that abnormal ventricular repolarization predisposes to atrial arrhythmias, it is unknown whether abnormal frontal QRS‐T angle is associated with an increased risk of atrial fibrillation (AF). Methods: We examined the association between frontal QRS‐T angle and AF in 4282 participants (95% white; 41% male) from the Cardiovascular Health Study (CHS). QRS‐T angle was computed from baseline electrocardiogram data. Abnormal QRS‐T angle was defined as values greater than the sex‐specific 95th percentile (men >131°; women: >104°). AF cases were identified from study electrocardiograms and from hospitalization discharge data through December 31, 2010. Cox regression was used to compute hazard ratios (HR) and 95% confidence intervals (CI) for the association between abnormal QRS‐T angle and AF. Results: Over a median follow‐up of 12.1 years, a total of 1276 (30%) participants developed AF. In a Cox regression model, adjusted for socio‐demographics and known AF risk factors, abnormal QRS‐T angle was associated with a 55% increased risk of AF (HR = 1.55, 95%CI = 1.23, 1.97). When QRS‐T angle was examined as a continuous variable, each 10° increase was associated with a 3% increased risk of AF (HR = 1.03, 95%CI = 1.01, 1.05). This finding was consistent in subgroups stratified by age, sex, and race. Conclusion: Our findings suggest that an abnormal frontal QRS‐T angle on the electrocardiogram provides important prognostic information regarding AF risk in the elderly, and further implicate ventricular repolarization abnormalities in the pathogenesis of AF.